Genetic Factors of Renin–Angiotensin System Associated with Major Bleeding for Patients Treated with Direct Oral Anticoagulants - Jeong Yee; Tae-Jin Song; Ha-Young Yoon; Junbeom Park; Hye-Sun Gwak (Pharmaceutics, 2022)
The purpose of this study was to identify the renin–angiotensin system (RAS)-related genetic factors associated with bleeding and develop the bleeding risk scoring system in patients receiving direct oral anticoagulants (DOACs). This study was a retrospective analysis of prospectively collected samples from June 2018 to May 2020. To investigate the associations between RAS-related genetic factors and major bleeding, we selected 16 single nucleotide polymorphisms (SNPs) from five genes (namely, AGT, REN, ACE, AGTR1, and AGTR2). Multivariable logistic regression analysis was employed to investigate the independent risk factors for bleeding and to develop a risk scoring system. A total of 172 patients were included in the analysis, including 33 major bleeding cases. Both old age (≥65 years) and moderate to severe renal impairment (CrCl < 50 mL/min) increased the risk of bleeding in the multivariable analysis. Among RAS-related polymorphisms, patients carrying TT genotype of rs5050 and A allele of rs4353 experienced a 3.6-fold (95% CI: 1.4–9.3) and 3.1-fold (95% CI: 1.1–9.3) increase in bleeding, respectively. The bleeding risk increased exponentially with a higher score; the risks were 0%, 2.8%, 16.9%, 32.7%, and 75% in patients with 0, 1, 2, 3, and 4 points, respectively. Although this study is limited to a retrospective study design, this is the first study to suggest RAS-related genetic markers and risk scoring systems, including both clinical and genetic factors, for major bleeding in patients receiving DOAC treatment.